A study on mean anion gap over 6 hours after admission as a predictor of pediatric mortality in pediatric intensive care unit - Jain, Mayank; Jain, Priya; Lal, Sandeep Narayan; Ranjan, Vivek (International Journal of Scientific Reports, 2020)
Background: The aims of the study was to correlate change in anion gap at 0 and 6 hours of admission with mortality in pediatric intensive care unit (PICU). Methods: Fifty children up to 12 years of age, admitted in PICU were included in the study. Blood gas anion gap levels were taken at 0 and 6 hours of admission and change in anion gap was calculated. Final outcome was recorded. Results: Out of 50 patients enrolled in the study, 18 (36%) patients died and 32 (64%) survived. Mortality was higher in group with increased anion gap after 6 hours of admission as compared to survived. Change in anion gap was higher in expired patient as compared to survivors. Conclusions: Mortality was higher in group with increased anion gap after 6 hours of admission.